UNIVERSITY NOTES. (The Accounting Review, 1930)
Abstract The article provides information about developments in university departments of various universities and colleges of the U.S., as of March 1930. M. S. Carroll of the accounting department of Waco, Texas-based Baylor University will be working toward his Ph.D. at Chicago University this summer and the accounting courses will be conducted in his absence by Dunker Hudson, cashier of the University. Professor A. S. Lang is on leave this year studying at the University of Texas. He will return to the department in September. The auditing seminar is being conducted as a field course in auditing. Only students who have a high ranking and who have had seven or eight majors in accounting are admitted to the course. They are given work with a firm of certified public accountants and submit reports for which they receive a major credit. The course is proving highly satisfactory. Professor Lloyd Morey of the University of Illinois has been on leave of absence for the first semester. He spent several months in Europe studying university business procedures there and gathering material for his book on University and College Accounting, which he has just completed.